2020
DOI: 10.1093/gji/ggaa114
|View full text |Cite
|
Sign up to set email alerts
|

A potential post-perovskite province in D″ beneath the Eastern Pacific: evidence from new analysis of discrepant SKS–SKKS shear-wave splitting

Abstract: SUMMARY Observations of seismic anisotropy in the lowermost mantle—D″—are abundant. As seismic anisotropy is known to develop as a response to plastic flow in the mantle, constraining lowermost mantle anisotropy allows us to better understand mantle dynamics. Measuring shear-wave splitting in body wave phases which traverse the lowermost mantle is a powerful tool to constrain this anisotropy. Isolating a signal from lowermost mantle anisotropy requires the use of multiple shear-wave phases, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…Because SKS and SKKS have similar raypaths in the upper mantle, but diverge significantly in the lowermost mantle, an observation of discrepant splitting between SKS and SKKS phases from the same event (measured on the same seismogram) suggests a contribution from the deep mantle to one or both phases (e.g., Deng et al., 2017; Reiss et al., 2019). SKS‐SKKS splitting discrepancies have been previously documented beneath North America (e.g., Asplet et al., 2020; Lei & Wen, 2020; Lutz et al., 2020), although these studies have also shown that seismic anisotropy in the upper mantle, not the lower mantle, represents the primary contribution to SK(K)S splitting observations. Of the 78 SKS‐SKKS pairs we measured, a minority (18%) showed discrepancies between SKS and SKKS splitting intensity measurements (such that the 95% confidence regions for the measurements did not overlap).…”
Section: Resultsmentioning
confidence: 93%
“…Because SKS and SKKS have similar raypaths in the upper mantle, but diverge significantly in the lowermost mantle, an observation of discrepant splitting between SKS and SKKS phases from the same event (measured on the same seismogram) suggests a contribution from the deep mantle to one or both phases (e.g., Deng et al., 2017; Reiss et al., 2019). SKS‐SKKS splitting discrepancies have been previously documented beneath North America (e.g., Asplet et al., 2020; Lei & Wen, 2020; Lutz et al., 2020), although these studies have also shown that seismic anisotropy in the upper mantle, not the lower mantle, represents the primary contribution to SK(K)S splitting observations. Of the 78 SKS‐SKKS pairs we measured, a minority (18%) showed discrepancies between SKS and SKKS splitting intensity measurements (such that the 95% confidence regions for the measurements did not overlap).…”
Section: Resultsmentioning
confidence: 93%
“…Before estimating the shear wave splitting due to the lowermost mantle, we corrected each PKS waveform by using the SKS upper mantle modeling from Figure 3. There is some scatter in the observed PKS splitting measurements, as is typical for shear wave splitting studies (e.g., Asplet et al, 2020;Creasy et al, 2017;Deng et al, 2017;Grund & Ritter, 2020;Long, 2009;Lutz et al, 2020;Niu & Perez, 2004). Therefore, we stacked each PKS error surface (after upper mantle correction) using Stacksplit (Grund, 2017) and found best-fitting PKS splitting parameters (due to D″ seismic anisotropy) of ϕ = −85° ± 10° (ϕ = −41° in ray-centered coordinates, using the convention of Wookey et al, 2005 andNowacki andWookey, 2010) and δt = 0.4 s ± 0.1 s (Figure 5).…”
Section: Shear Wave Splitting Resultsmentioning
confidence: 98%
“…In other words, S waves that propagate perpendicularly with the fracture will come slower, while the S wave that is parallel to the fracture will come faster [28]. With further development, delay time (δt) will be bigger if the S wave propagates perpendicularly to the fracture, and it will be smaller if it propagates parallel or in line with the fracture [29].…”
Section: Parameter Shear Wave Splitting (Sws)mentioning
confidence: 99%